Event Hiburan bagi Tki di Taiwan sebagai Pencitraan pada Anggota Komunitas - Ulani Yunus (Humaniora, 2014)
Event is still a useful media for building good image for certain communities. In addition to functioning as a media ritual, an event which is published through a live broadcast mass media will also increase the brand image of a particular product. Research question in this article is: what are the kinds of the TKI Event held in Taiwan in 2013 and what elements of the event that brings TKI enthusiastic in Taiwan? The method used in this study is a qualitative interpretive. The data was collected through direct observations and impressions of social media such as youtube as well as literature from the source journal from previous research literature or books that support research topic. Conclusion of the study states that the type of event held by workers in Taiwan is a talent contest and stage entertainment. While elements of the event that brings enthusiastic for workers is an event that displays imagery figure, and the appearance of celebrities.